2021
DOI: 10.3389/fped.2021.764583
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the French National Lockdown on Admissions to 14 Pediatric Intensive Care Units During the 2020 COVID-19 Pandemic–A Retrospective Multicenter Study

Abstract: Background: After the COVID-19 pandemic reached France in January 2020, a national lockdown including school closures was officially imposed from March 17, 2020, to May 10, 2020. Pediatric intensive care units (PICUs) admit critically ill infants, children and teenagers with severe acute conditions, in particular infectious and traumatic diseases. We hypothesized that PICU admissions would be considerably modified by the lockdown.Aims: The objectives of the study were to describe the type of admissions to Fren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…There was nearly a 50% decrease in general in the number of PICU admissions, and this can be important preliminary information for securing hospital beds in the event of a future pandemic or disaster, for instance, as a consequence of SDMs. These results have been confirmed by other studies published more recently (98)(99)(100).…”
Section: Discussionsupporting
confidence: 89%
“…There was nearly a 50% decrease in general in the number of PICU admissions, and this can be important preliminary information for securing hospital beds in the event of a future pandemic or disaster, for instance, as a consequence of SDMs. These results have been confirmed by other studies published more recently (98)(99)(100).…”
Section: Discussionsupporting
confidence: 89%
“…After the introduction of strict non-pharmaceutical public health measures in France during the first COVID-19 pandemic wave in February to March 2020, widespread circulation of RSV ceased and PICU admissions for bronchiolitis decreased significantly [ 26 32 ]. One study found an 85.3% reduction in PICU admissions for bronchiolitis between September and December 2020 versus predicted admissions [ 32 ], while another study found a 36% decrease in admissions for respiratory viral infections from March to May 2020 compared with admissions in March to May 2019 [ 31 ]. However, a delayed RSV epidemic, relatively small and short, occurred in France in early 2021 after the relaxation of the measures (Fig.…”
Section: Epidemiology and The Impact Of Non-pharmaceutical Interventionsmentioning
confidence: 99%
“…This situation has become more common since the onset of the COVID-19 pandemic owing to variations in childcare facilities, systems, and confinement periods. 2 Here, we report a case of acute ethanol intoxication in an infant to illustrate these issues.…”
mentioning
confidence: 96%